Higher Education Policy for Tackling Climate Change
XVIII, 284 p. 15 illus.
Keywords: “What role is higher education playing in addressing the climate crisis? Through a critical analysis of higher education policies on climate change and institutional responses in nine countries, this innovative volume illuminates very different national experiences that are sometimes hopeful but frequently weak and symbolic. This important book provides a darkly unsettling portrait of policy ambiguity and unfulfilled potential in the face of our greatest challenge.” —Glen A. Jones, Professor of Higher Education and former Dean, Ontario Institute for Studies in Education, University of Toronto, Canada. This book investigates the roles of universities and other types of higher education institutions in tackling climate change. Climate change is arguably the most pressing concern of our era, and one of the biggest challenges humanity has faced. In line with this, there is a firm belief that higher education institutions are among the key actors in the fight against climate change, especially in providing innovations and new technologies to mitigate the issue. A steadily growing number of universities across the world are playing a leading role in the fight for a sustainable world. Bringing together scholars from around the world, this volume adopts an interdisciplinary approach to investigate the effects resulting from the complex interplay between national, regional and global higher education policy initiatives aimed at tackling climate change. It will appeal to all those interested in climate change, science and innovation, public policy and higher education governance. Chapters 1, 2 and 8 are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com. Jouni Kekäle is Chief Senior Specialist and a Professor at the University of Eastern Finland. His research interests include academic leadership, human resource management, and organizational cultures in higher education. Rómulo Pinheiro is Professor of Public Policy and Administration and Deputy Head of Department at the University of Agder, Norway. His research interests are located at the intersection of public policy and administration, organizational theory, economic geography, innovation and higher education studies.